2016
DOI: 10.4037/ajcc2016269
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Critically Ill Patients: Relationship to Sedation

Abstract: Objectives To describe the number and type of stimulation events and the relationship of stimulation to sedation level in patients receiving mechanical ventilation. Methods A 4-hour direct observation was conducted in 103 patients receiving mechanical ventilation. Stimulation events and sedation level before and after the stimulation were documented. Eight categories of stimulation events were developed in a previous pilot study of 36 patients receiving mechanical ventilation. Sedation was measured continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We found a significant correlation between the PSI and the RASS, which is expected and not surprising given that both methods are used for sedation depth measurement. The arousability by stimulation in the sedated ICU patients correlates with the depth of sedation, as measured with the RASS and expressed via the PSI [ 50 ]. Interestingly, a closer look reveals inconsistencies: the RASS does not adequately reflect the clinically observed depth of sedation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a significant correlation between the PSI and the RASS, which is expected and not surprising given that both methods are used for sedation depth measurement. The arousability by stimulation in the sedated ICU patients correlates with the depth of sedation, as measured with the RASS and expressed via the PSI [ 50 ]. Interestingly, a closer look reveals inconsistencies: the RASS does not adequately reflect the clinically observed depth of sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a closer look reveals inconsistencies: the RASS does not adequately reflect the clinically observed depth of sedation. The PSI values obtained indicated a much lower RASS (e.g., −5) than that determined in the clinical examination (−3/−4) [ 50 ]. Regarding the sedation of critically ill patients, there exists no consensus on the method to be used.…”
Section: Discussionmentioning
confidence: 99%
“…The selected sixty participants were randomly and equally allocated to either a control or an intervention group through block randomization [11]. Sampling conducted based on random block process by computer.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Sensory stimulation is a therapeutic method which stimulates the reticular activating system in the brain and facilitates the reorganization of brain activities through creating new neural links [10]. Auditory stimulation is one of the sensory stimuli which can be provided to patients in ICU by their family members or nurses [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hearing is the most important sense for understanding peace and security and the last sense that disappears in comatose patients; unlike other senses, there is no obstacle to stimulate this sense (27). Grap et al (28) found that auditory stimulation affects the management of agitation. Administering the right sedation is one of the essential roles of nurses in relation to mechanically ventilated patients admitted to ICU (29).…”
Section: Introductionmentioning
confidence: 99%